Bolts, double hexagon head, close tolerance shank, medium length thread, in heat resisting nickel base alloy NI-P101HT (Waspaloy), for increased height nuts. Classification: 1210 MPa (at ambient temperature)/730°C. (15th June 1996) - British Standards Institution,
No abstract available